A Novel Rat Tail Needle Minimally Invasive Puncture Model Using Three-Dimensional Printing for Disk Degeneration and Progressive Osteogenesis Research - Xia, Dongdong; Yan, Meijun; Yin, Xin; Hu, Wenhao; Zhang, Chi; Hu, Baiwen; Ge, Ting; Wu, Xiaochuan; Xiao, Jin; Gao, Liang; Liu, Junqi; Tan, Jun (Frontiers in Cell and Developmental Biology, 2021)
Many studies focused on the annulus fibrosus (AF) injury in rodent tail model for the intervertebral disc degeneration (IDD) research. However, previous studies caused tremendous injury of intervertebral disc (IVD) by penetrating whole disc. This study aimed to build a progressive IDD rodent tail model by a novel device for precise and minimally invasive puncture in AF.A precise puncture device was customized by 3D Printing Technique. 40 rodent tail IVDs were randomly grouped as follows: group A, non-puncture; group B, annulus needle puncture (ANP) for 4 week; group C, ANP for 8 week; and group D, ANP for 12 week. Pre- and post-puncture IVD height on radiographs and IVD signal intensity on T2 magnetic resonance imaging (MRI) were measured. Average bone density (ABD) on the end of coccygeal vertebrae between punctured disc was measured on the radiographs. Hematoxylin and eosin, TUNEL staining methods, immunofluorescence for cleaved-caspas3 and immunohistochemistry for aggrecan and collagen II were performed. Progressively and significantly increasing IVD height loss and degenerative grade were observed following the time points. The ABD was respectively 81.20±4.63 in group A, 83.93±3.18 in group B, 92.65±4.32 in group C, 98.87±6.69 in group D. In both group C and group D, there were significant differences with group A. In histology, increasing number of AF cells was noted in group B. In both group C and D, the fissures in AF were obviously observed, and a marked reduction of AF cells were also observed. In all ANP groups, there were significant decrease in number of NP cells, as well as aggrecan and collagen II contents. TUNEL assay showed cellular apoptosis were stimulated in all puncture group, especially in group D.A progressive IDD rat model could be standardly established by the micro-injury IVD puncture using a novel 3D printing device. This animal model provided a potential application for research of progressive hyperosteogeny following IDD development.